Related differences in fecal bacteria of Chinese northern pregnant women of different ages: associations with maternal clinical indicators and neonatal outcomes - Feifei Hu; Gaona Liu; Xin Sun; Yao Su; Mingli Huang (Frontiers in Microbiology, 2025)
The gut microbiota, a vital “microbial organ,” influences digestion, immunity, and metabolism. Aging alters gut microbiota of pregnant women through metabolic and hormonal pathways, thereby impacting neonatal health. In this study conducted in northern China, we compared two groups: advanced maternal age (AMA, ≥35 years) and younger maternal age (YMA, 20–34 years), analyzing fecal bacteria and maternal metabolism via biomarker measurements and microbial sequencing. Results showed AMA had significantly higher serum levels of alkaline phosphatase (AKP), 25-hydroxyvitamin D [25(OH)D], and creatinine, while YMA exhibited higher Cu but lower Fe concentrations. Although the fecal bacteria of AMA participants showed greater diversity, the YMA group displayed a more stable bacterial composition, characterized by a higher abundance of beneficial bacteria (e.g., Bifidobacterium) and a lower prevalence of potential pathogens (e.g., Streptococcus). Metabolically, the fecal bacterial network in YMA participants was more integrated, whereas the AMA group showed a “high-complexity, low-efficiency” pattern with disrupted metabolic pathways, which may contribute to adverse pregnancy outcomes. This study highlights age-related dysbiosis of the fecal bacteria in pregnant women and its impact on maternal and neonatal health, advocating for personalized prenatal care strategies for women with AMA.